(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Cleaner fish are specialized fish species that coexist with other marine organisms by removing parasites and debris from their bodies. These fish play a crucial role in maintaining the health of various marine species, including reef manta rays (Mobula alfredi). However, a limited understanding of their interactions presents a significant challenge in marine conservation. This study aims to identify the species of cleaner fish that interact with reef manta rays (M. alfredi) at Manta Sandy, Dampier Strait, Raja Ampat. A modified camera trap method was employed, utilizing three GoPro cameras strategically placed at different locations within the study site. Data collection was conducted over 14 days in February 2023 to document cleaner fish interactions with reef manta rays. The findings revealed the presence of three cleaner fish species at the Manta Sandy Cleaning Station: Labroides dimidiatus, Thalassoma lunare, and Chaetodon kleinii. This study highlights the diversity of cleaner fish species at Manta Sandy, contributing valuable insights into their ecological roles and conservation significance. The findings serve as a crucial reference for future research on marine biodiversity conservation in Raja Ampat and surrounding regions.